Efeito da moagem de alta energia na densificação e microestrutura do compósito Cu-C sinterizado em estado sólido - Lourenço, Cleber da Silva (2018)
Copper-graphite composite (Cu-C) is widely used as electrical contacts where the copper phase provides the property of electrical conductivity and the graphite phase, the lubrication properties. This system is immiscible and its components are mutually insoluble, hanpered your consolidation. High energy ball milling (MAE) is good to produce nanostructured, amorphous and solid solubility powders or increase solid solubility, in addition to producing high homogeneity of the phases and composition of the particles. Particle size, phase dispersion and sintering atmosphere are factors that affect the densification and microstructure of the Cu-C composite. Therefore, this work investigated the influence of milling time on the decrease in size and dispersion of Cu-10% pC composite phases. The effect of temperature and sintering atmosphere on density and microstructure of the samples sintered was also investigated. Powder-composites they are prepared by MAE and mechanical mixing. In the first case, powders they are prepared with ethyl alcohol in a Pulverissete 7 planetary mill with carbide balls at 400 rpm for 50 hours. The ball to powder ratio by weight 1: 4. In the other case, the powders have been placed in a plastic container and mixed manually for 5 minutes. Soon after the powders are compacted in a uniaxial matrix at 200 MPa and sintered in a conventional tube furnace resistive and with a dilatometric register at 800, 1000 and 1050 ° C for 1 h of isotherm and under atmospheres of argon, H2 and a mixture of argon and H2 . Powder have also been spark plasma sintering at 900°C. The initial powders and prepared by ball milling and mechanical mixing, as well as the sintered compacts were characterized by optical microscopy, scanning electron microscopy, dispersive energy spectroscopy, X-ray diffraction and particle size analysis. The density of the green and sintered bodies were measured by the geometric method (weight / volume). Vickers microhardness measurements were also performed on the sintered samples. The sintered samples under H2 atmosphere presented low density and mechanical resistance. differently, the sintered bodies in the dilatometer at 800 ° C and 1000°C for 1 hour under an argon atmosphere became denser, but their density only reached 60.40% of theoretical density. A density greater than 82% of the theoretical density was achieved by spark plasma sintered samples and, as expected, the microstructures of samples sintered with mechanically mixed powders are completely different from the microstructures of the milling powders and exhibit high heterogeneity.